Subtropical fruits: Guavas - de Almeida Teixeira, Gustavo Henrique [UNESP] (Elsevier, 2020)
Guava (Psidium guajava L.) fruit can have climacteric or suppressed climacteric behavior, depending on the cultivar. Guava fruit have a short shelf-life mainly due to rapid ripening rate and high susceptibility to decay, mechanical damage, and chilling injury. The fruit can be stored for up to 2–3 weeks at 7–10°C, and 85–90% relative humidity (RH), but fresh weight loss can be a problem. The application of 1-MCP can provide some improvement in storability. The beneficial effects of CA with low O2 and/or high CO2 levels include reduction in respiration rates and ethylene production, color change, and softening, retention of vitamins, sugars and organic acids as well as the inhibition of some physiological disorders, and diseases. Guava fruit do not tolerate CO2 levels higher than 10%. Even though some studies have reported CA/MA storage for guava fruit, many biochemical responses remain unclear and more investigations are required to fully understand the impact of O2 and CO2 on respiration and ethylene production, and their influence on shelf-life.
Keywords: Guava; Modified atmosphere packaging; Quality; Shelf-life; Storage